Five years after «Laudato si’». Ecological synodality - Lorenzo Francisco, Ángel Luis (Razón y fe, 2021)
This article is intended as an invitation to read again Pope Francis’ first social Encyclical, Laudato si’, on its fifth anniversary. It shows the journey of these five years, from a necessary synodal point of view. It proposes an attitude of listening and dialogue, starting off from a theology of reality. And walking together to continue building the future, through concrete and active participation. Being witnesses-protagonists of this challenge, in the midst of a world constantly changing, requires an urgent renewal. Yet we united under a double cause: the care of human dignity and the care of our common home.
Keywords: synodality; Laudato si’; participation; integral ecology